Assessment of vegetation health index (VHI) using Modis data in rivers state, Nigeria - M. Menegbo, Emmanuel (International Journal of Advanced Geosciences, 2024)
Droughts have a significant impact on agricultural and agro-pastoral regions as they heavily rely on rainfall. Monitoring agricultural drought is of utmost importance to ensure global food security. Satellite remote sensing has emerged as a reliable method for assessing vegetation health and has proven to be an effective approach for detecting droughts on a global scale. Various indices, such as the Normalized Differ-ence Vegetation Index (NDVI), Land Surface Temperature (LST), Vegetation Condition Index (VCI), and Vegetation Health Index (VHI), have been developed using remote sensing data. These indices are utilized to identify and monitor agricultural droughts by examining the vegetation and plant growth. The study employed MODIS data and leveraged Google Earth Engine to process it using codes before export-ing it to QGIS for visualization. The results revealed a mean value of 4.8(5) for VHI and 4.7(5) for VCI, indicating the absence of drought conditions. This signifies that the region is suitable for agricultural activities. Additionally, a TCI value of 4 indicated mild vegetation stress. It is advisable to continuously monitor the VHI over Rivers State for effective planning, decision-making, and providing guidance to local farmers.
Keywords: Rivers State; Vegetation Condition; Droughts; Vegetation Health; Agricultural.